Patient consent in the post-Montgomery era: A national multi-speciality prospective study. Issue 5 (October 2019) - Knight, Stephen R.; Pearson, Robert; Kiely, Ciara; Lee, Grace; MacDonald, Alisdair J.; Macdonald, Angus; ,
Abstract: Background: The Montgomery ruling has had a wide-ranging impact on the consent process and has been the subject of new guidelines by bodies, including the Royal College of Surgeons (RCSEng). This is the first study to examine the current standard of consent for surgical procedures at a national level. Method: A national collaborative research model was used, with prospective data collection performed across hospitals in Scotland. Variables associated with the consent process were audited across three surgical specialities (general surgery, urology and orthopaedics) and measured against standards set by RCSEng, the Scottish Public Services Ombudsman and medical defence organisations. Results: A total of 289 cases were identified from 12 hospitals. The majority of patients were reviewed by a consultant surgeon in clinic (79.9%) or on the day of surgery (55.4%). The clinic consent rate was 27.0%, while a copy of the documented discussion was only provided to 4.2% of patients. On the day of surgery, the benefits, risks and alternatives to the planned procedure were discussed in less than half of cases. This rate was similar across different clinician grades, while marked variation was seen across hospitals. Conclusion: In this prospective multi-centre study we have demonstrated wide variation in the consent processes in many surgical specialities across Scotland. Following the Montgomery ruling, we have demonstrated the current consent process in elective surgery is likely to be substandard, and may require additional steps to be taken by clinicians to ensure patients are fully informed to make decisions regarding their treatment. Highlights: This is the largest study of consent process following the Montgomery ruling. A collaborative model was used in partnership with two medico-legal advisors. 289 elective cases were analysed across the majority of Scottish hospitals. Significant variation in consent process existed across hospitals and specialities. Current consent processes are substandard and require urgent attention.